Applications of CRISPR-Cas for synthetic biology and genetic recording. Issue 5 (October 2017) - Schmidt, Florian; Platt, Randall J.
Abstract: The epic arms race between microbes and their predators was the driving force behind the evolution and diversification of the truly remarkable microbial adaptive immune system CRISPR-Cas. CRISPR-Cas systems mediate defense through three stages: recording of nucleic acid species, multiplexed RNA expression and processing, and eventually RNA-guided cleavage of hostile genetic elements. The entire process is orchestrated by a plethora of effector proteins endowed with specialized functions for manipulating genetic material. Investigating this treasure trove substantially fostered the development of the RNA-guided DNA endonuclease Cas9 into a versatile molecular tool for synthetic biology and biomedicine. Here, we review the developments of Cas9 and other CRISPR-Cas components for applications in synthetic biology as well as highlight emerging CRISPR-Cas-based genetic recorders and memory devices. Graphical abstract: Highlights: The CRISPR-Cas system revolutionized genome editing and biomedicine. CRISPR-Cas system components can be engineered into useful synthetic biology parts. CRISPR-Cas adaptation and interference proteins can be applied as genetic recorders. Genetic recorders facilitate molecular barcoding and cellular lineage tracing. Inducible genetic recording provides a cellular memory of biological activity.